Analisis Perbandingan Kualitas Proximate Batubara Pada PIT B1 dengan ROM Coal Stockpile KM4 di PT. Trisensa Mineral Utama Kecamatan Loa Janan Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Ardian Saputra; Windhu Nugroho; Henny Magdalena; Agus Winarno; Albertus Juvensius Pontus (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Coal quality must be controlled from the pit area to the ROM stockpile to ensure compliance with market specifications. However, hauling and stockpiling processes often lead to changes in coal characteristics. This study aims to analyze variations in proximate parameters between coal from Pit B1 and ROM Stockpile Km4 at PT Trisensa Mineral Utama and to identify factors contributing to these changes. The methodology includes field sampling at both locations, sample preparation based on ASTM standards, and laboratory testing of inherent moisture, residual moisture, ash content, volatile matter, and fixed carbon. The results indicate that coal undergoes quality changes after being stored in the stockpile, marked by a decrease in inherent moisture of 2.54% (from 17.64% to 15.10%), a decrease in residual moisture of 1.42% (from 17.17% to 15.75%), a slight reduction in ash content of 0.16%, a decline in volatile matter of 0.28%, and a reduction in fixed carbon of 0.18%. These changes are influenced by field conditions, material contamination during mining, rainfall, coal porosity, and handling activities at the stockpile. The findings highlight the need for improved sampling management, better surface water control, and stricter material handling procedures to minimize coal quality degradation.